RANS Flow Computation around Transonic RAE2822 Airfoil with a New SST Turbulence Model (MIST International Journal of Science and Technology, 2025)
The solution to RANS (Reynolds-averaged Navier-Stokes) equations invokes a suitable framework for turbulence modelling. To account for turbulence and transition effects, a new SST (Shear Stress Transport) k-ω turbulence model is coupled with RANS to simulate the transonic flow passing an RAE2822 air foil. Three sets of experimental data of the super-critical RAE2822 air foil are employed to validate the new SST (NSST) closure. Computations are conducted for a limited range of Reynolds numbers with variable angle of attack. The NSST model has been found to replicate satisfactory results for lift CL and drag CD coefficients as well as for skin-friction and pressure coefficient profiles under considerable shock-wave boundary layer (BL) interaction, although CD is challenging to be accurately predicted since the turbulence model requires to adequately resolve near-wall turbulence in the BL with varying pressure gradients. NSST predictions are compared with those of the widely-used SST k-ω model. Numerical outputs demonstrate that the included NSST transition model plays no significant roles to appropriately predict CL and CD, indicating that the NSST performance is almost equivalent to that of the SST in the current analysis.MIJST, Vol. 12, December 2024 : 23-28DOI: https://doi.org/10.47981/j.mijst.12(02)2024.477(23-28)